2013
DOI: 10.1007/s12262-013-0957-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Trauma and Immune Functional Changes Following Major Lung Resection

Abstract: Video-assisted thoracic surgery (VATS) has evolved greatly over the last two decades. VATS major lung resection for early stage non-small cell lung carcinoma (NSCLC) has been shown to result in less postoperative pain, less pulmonary dysfunction postoperatively, shorter hospital stay, and better patient tolerance to adjuvant chemotherapy compared with patients who underwent thoracotomy. Several recent studies have even reported improved long-term survival in those who underwent VATS major lung resection for ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 51 publications
1
15
0
1
Order By: Relevance
“…NK cells were found to be lower post-operatively along with T cells and NKT cells and this effect was more pronounced in patients undergoing major surgery versus minor surgeries. Similarly, in non-small cell lung cancer patients NK cells were found to be significantly lower in patients undergoing open thoracotomy (major) versus video-assisted thoracoscopic lobectomy (minor) [ 89 ].…”
Section: Surgical Stress Inflammation and Natural Killer Cell Dysmentioning
confidence: 99%
“…NK cells were found to be lower post-operatively along with T cells and NKT cells and this effect was more pronounced in patients undergoing major surgery versus minor surgeries. Similarly, in non-small cell lung cancer patients NK cells were found to be significantly lower in patients undergoing open thoracotomy (major) versus video-assisted thoracoscopic lobectomy (minor) [ 89 ].…”
Section: Surgical Stress Inflammation and Natural Killer Cell Dysmentioning
confidence: 99%
“…Swanson [13] and others have found that video-assisted thoracoscopic surgery can achieve the objective of The study found [14][15] that surgical trauma could inhibit somatic cell immunity and humoral immunity. degree of trauma [16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, VATS approach for LC may allow for a better preservation of the patient's immunity and optimize long-term survival (48). The potential advantages of minimally invasive major pulmonary resection may be explained by various mechanisms.…”
Section: Vats Surgery Of Lung Cancer As the Way To Reduce Perioperatimentioning
confidence: 99%
“…The association between a better preserved immune status following minimal invasive VATS resection for early stage NSCLC and improved survival remains a fantasy for the skeptics, as emphasized by C. Ng and K. Lau (48). In order to demonstrate such a relationship, authors suggested a large randomized trial that measures a comprehensive range of postoperative immune markers and a long-term survival following VATS and open lobectomy.…”
Section: Vats Surgery Of Lung Cancer As the Way To Reduce Perioperatimentioning
confidence: 99%